EFFECT OF HAREETAKYADI YOGA IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE – PRE TEST-POST TEST DESIGN (International Journal of Ayurveda and Pharma Research, 2021)
Chronic Obstructive Pulmonary Disease (COPD) is a lung disease characterized by chronic obstruction of lung airflow that interferes with normal breathing, which is progressive and is not fully reversible. COPD includes chronic bronchitis and emphysema. Symptoms of COPD are well explained in Ayurveda in the context of Kasa and Swasa among which chronic bronchitis can be better correlated to Vataja and Kaphaja kasa and emphysema to Tamaka swasa. COPD is characterized by mucous hyper secretion, airway narrowing, fibrosis and destruction of lung parenchyma. Even though the existing conventional management is excellent, Ayurveda provides additional benefits such as improvement in quality of life. The study drug Hareetakyadi yoga is mentioned in Prakarana of kasa in Chikitsa manjari. The objective of the study was to evaluate the Effect of Hareetakyadi yoga in Chronic Obstructive Pulmonary Disease. The Study includes 10 subjects of age group 40-70 years of both gender, diagnosed clinically and as per investigations satisfying COPD, stage 1 & 2 as per GOLD criteria of spirometry attending department of Kayachikitsa, Government Ayurveda College, Thiruvananthapuram. A protocol from Deepana to Virechana were done as preparatory phase before administering drug. Hareetakyadi yoga having the properties of Kapha vata hara, Agni deepana and Rasayana property seems to be effective in the management of this disease.